Biotechnology in Tree and Bamboo Improvement - Venkatesh, C. S. (Indian Forester, 1992)
No doubt the new techiques of biotechnology such as tissue culture, parasexual hybridization through protoplast fusion, haploid production and genetic engineering hold promising potential in future genetic tree improvement work. However, a number of hurdles still remain to be crossed before they can be adopted as standard techniques in agricultuntl crop and tree improvement work. Further, in the foreseeable future these new techniques will most likely be used as adjuncts to rather than a replacement of conventional tree breeding methodology. For, unlike crop species, forest trees have not been domesticated before and therefore retain in themselves a good deal of natural genetic Vlriability. Therefore, while persisting with traditional tree improvement methods, progressive tree breeders also need to keep in touch with current and future developments in the exciting new field of biotechnology and should be on the lookout for their possible applications in their work.